Kaidah Tafsir: Keistimewaan Al-Asma’ Al-Husna Diakhir Ayat Al-Qur’an - Zulfikar, Eko (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
This paper discusses the rules of interpretation of the privileges of al-asma’ al-husna at the end of the verses of the Qur’an. By using the ulumul Qur’an approach and interpretation knowledge, it was found that the mention of al-asma’ al-husna at the end of the verse of the Qur’an has significant features. Al-Qur’an verses containing al-asma’ al-husna at the end of the verse show the attributes of the great God. The content of the meaning that has been explained al-Qur'an, when accompanied by the names of Allah al-asma’ al-husna indicate His greatness and power. In addition, the explanation of the verses of the Qur'an which shows the mercy, taufik, guidance and maghfirah of Allah always ends with His names which contain the attributes of Rahman and Rahim (love). While in the verses of al-Qur’an related law, retribution, punishment, and torment closed with the names of God which includes the nature of Might, Power, Wisdom, Science, and His Power.